2007
DOI: 10.1007/s12031-007-0006-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging, dietary restriction and glucocorticoid treatment on housekeeping gene expression in rat cortex and hippocampus—Evaluation by real time RT-PCR

Abstract: Dementia of the Alzheimer type (DAT) is associated with the accumulation of beta-amyloid (A beta) peptides derived from beta-amyloid precursor protein (APP). Goldstein and coworkers have suggested that APP acts as a cargo receptor connecting post-Golgi vesicles and motor proteins. Sisodia and colleagues have suggested that APP is a passive passenger within the vesicles. Both views predict that one should be able to visualize colocalizations of APP with microtubules, the object of the present investigation. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 33 publications
3
60
0
6
Order By: Relevance
“…Overall, our study demonstrates that UBC, YW-HAZ, RPLP and TBP, were the most suitable reference genes to be used for gene expression studies using MCF7, HCT116 and HepG2 cells. Although GAPDH and ACTB are used as reference genes in most in vitro studies using these cell lines (Bracke et al 1993;Tanic et al 2007;Cicinnati et al 2008;Mori et al 2008), these two reference genes did not exhibit stable expression levels across MCF7, HCT116 and HepG2 cells, as demonstrated by our current results as well as previous studies (Schmittgen and Zakrajsek 2000;Gorzelniak et al 2001). The GAPDH and ACTB genes are variably expressed when subjected to serumstimulation (Schmittgen and Zakrajsek 2000) and hormone treatments (Gorzelniak et al 2001).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Overall, our study demonstrates that UBC, YW-HAZ, RPLP and TBP, were the most suitable reference genes to be used for gene expression studies using MCF7, HCT116 and HepG2 cells. Although GAPDH and ACTB are used as reference genes in most in vitro studies using these cell lines (Bracke et al 1993;Tanic et al 2007;Cicinnati et al 2008;Mori et al 2008), these two reference genes did not exhibit stable expression levels across MCF7, HCT116 and HepG2 cells, as demonstrated by our current results as well as previous studies (Schmittgen and Zakrajsek 2000;Gorzelniak et al 2001). The GAPDH and ACTB genes are variably expressed when subjected to serumstimulation (Schmittgen and Zakrajsek 2000) and hormone treatments (Gorzelniak et al 2001).…”
Section: Discussionsupporting
confidence: 71%
“…Variability may also occur when cellular signalling pathways and basic cell metabolism are disturbed (Singh and Green 1993). In addition, the expression of these reference genes may be influenced by experimental conditions (Thellin et al 1999;Selvey et al 2001;Tricarico et al 2002;Arukwe 2006;Valenti et al 2006;Tanic et al 2007), drug and hormone treatments (Bustin 2000;Gorzelniak et al 2001;Huggett et al 2005). Therefore, appropriate reference genes need to be identified and validated for every experimental design.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic drift likely occurs during aging and results in altered gene expression patterns that compromise function and cellular adaptations to environmental stimuli (Desjardins et al, 1997), including stimuli that are related to learning and memory (Burke and Barnes, 2006;Tanic et al, 2007). For example, a recent study found that age-related decreases of Arc gene transcription in the hippocampus is mediated by DNA methylation and results in decreased gene transcription, decreased plasticity, and disruptions in memory storage and retrieval processes (Penner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, degeneration of normal aging or simple dietary restriction will alter expression of 18S rRNA within the rodent hippocampus and neocortex (Tanic et al, 2007). In models of injured dorsal root ganglion cells (Willis et al, 2005) and hippocampal ischemia (Farwell et al, 1998), b-actin mRNA also shows alteration from control expression levels.…”
Section: Altered Reference Gene Expression and Cns Traumamentioning
confidence: 99%